2016
DOI: 10.1108/ejm-06-2014-0346
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes a celebrity holding a negative public image is the best product endorser

Abstract: Purpose The purpose of this paper is to examine women’s reactions to celebrity endorsers holding positive and negative public images and the consequences for purchase intentions of the endorsed product. Design/methodology/approach The paper draws on the social comparison literature and applies the theory of upward and downward comparisons to the celebrity endorsement context. Findings Study 1 shows that exposure to celebrities holding a positive public image decrease consumers’ temporal self-esteem, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 49 publications
0
23
0
8
Order By: Relevance
“…Wang and Scheinbaum () found that consumers’ positive perception of a celebrity endorser's physical attractiveness enhances brand attitude and purchase intentions. Conversely, Sääksjärvi, Hellén, and Balabanis () found that for low‐self‐esteem consumers, exposure to a good‐looking celebrity affects purchase intentions negatively.…”
Section: A Proposed Prescriptive Model: Comprehensive Celebrity Endormentioning
confidence: 99%
“…Wang and Scheinbaum () found that consumers’ positive perception of a celebrity endorser's physical attractiveness enhances brand attitude and purchase intentions. Conversely, Sääksjärvi, Hellén, and Balabanis () found that for low‐self‐esteem consumers, exposure to a good‐looking celebrity affects purchase intentions negatively.…”
Section: A Proposed Prescriptive Model: Comprehensive Celebrity Endormentioning
confidence: 99%
“…Among many popular advertising strategies, celebrity endorsement has been rising as an appropriate promotional trend with an important role in the success of the product in terms of sales and brand recognition. However, some previous studies show that an attractive celebrity image sometimes decrease purchase intention [3].…”
Section: Literature Reviewmentioning
confidence: 97%
“…Moreover, the attractive celebrity may create a negative effect on mood and body image [2]. Finally, sometimes the celebrities holding a positive public image diminish purchase intentions when consumers are low in true self-esteem [3].…”
Section: Introduction *mentioning
confidence: 99%
“…It has been implicitly implied that the consumer is in favor of endorsement, achieved through the exposure to beautiful and famous people. The effects of this exposure, however, are not always positive, and unconscious comparisons with the idealized images of the celebrities could provoke negative emotions (Brown and Tiggemann, 2016; Sääksjärvi et al, 2016; Van de Ven, 2017). There are, moreover, inconsistent views about the types of celebrities who induce these emotions.…”
Section: The Consequences Of Celebrity Endorsement: the Need For A Bimentioning
confidence: 99%